Hardiness Personality and Family Support for Women’s Quality of Life with Breast Cancer - Supatmi, Supatmi; Reliani, Reliani; Afiyah, Raden Khairiyatul; Ernawati, Ernawati (Gaceta Médica de Caracas, 2023)
Introduction: Breast cancer diagnosis and treatment can lead to psychological changes such as stress and depression, which significantly impact the quality of life. Psychological hardiness and family support are two necessary health-elevating factors that strengthen individuals to remain both psychologically and physically healthy despite encountering negative life events such as breast cancer. Objective: This study investigated the relationship between hardiness personality and family support on the quality of life in women with breast cancer.